Marriage and morals - Russell, Bertrand (Routledge classics, 2009)
Marriage and Morals is a compelling cross-cultural examination of individual, familial and societal attitudes towards sex and marriage. By exploring the codes by which we live our sexual lives and conventional morality, Russell daringly sets out a new morality, shaped and influenced by dramatic changes in society such as the emancipation of women and the wide-spread use of contraceptives. From the origin of marriage to the influence of religion, Russell explores the changing role of marriage and codes of sexual ethics. The influence of this great work has turned it into a worthy classic.